Robotic Systems in Current Clinical Practice - Avgousti, Sotiris; Christoforou, Eftychios G.; Panayides, Andreas S.; Masouras, Panicos; Vieyres, Pierre P.; Pattichis, Constantinos S. (My University, 2020)
Medical robotic systems are successfully employed in various surgical specialties today. Yet, a substantial number of remarkable systems that have been developed and piloted, have failed to reach commercialization and thus adoption in clinical practice. This is partly due to the strict regulatory requirements, which typically occupy a significant amount of the development time while incurring additional costs. Pertinent to regulatory approvals is the field of Human Factors, which plays a central role in the design of safe and efficient medical devices. This study briefly introduces the FDA regulatory approval process, discusses the role of human factors in the design process and highlights specific robotic systems that have obtained approval for clinical use. The purpose is to show the status of robotic technologies in relation to the current clinical practice.
Keywords: Human Factors; Medical Robotics; Regulatory Approvals; Robotic Surgery